Pemanfaatan Tempurung Kelapa Menjadi Briket Sebagai Biomassa Alternatif Ramah Lingkungan - Yunus, Andi Ibrahim; Masruniwati, Afifah; Indrayuni, Armi; Fatimah, Andi; A. Sompa, A. Sompa (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Indonesia as an agricultural country has the largest potential for coconut utilization in the world. Coconut shells are agricultural waste which is one of the sources of biomass energy processed into briquettes. The purpose of making charcoal briquettes from coconut shells is to create an environmentally friendly alternative energy source. The method of implementing the activity is in the form of community outreach for 10 participants in Balla Tinggia Hamlet in 2025, which aims to outline the plans carried out by presenting material including the stages of processing coconut shell waste into environmentally friendly briquette fuel. The work program for this activity, namely: observation, planning, implementation and assistance of activities, and evaluation of activity results. further drying, and packaging and storing briquettes. Based on interviews with the people of Balla Tinggia Hamlet, they expressed their appreciation for the success of this activity, enthusiastically following several stages of the activity carried out, so that they felt capable of doing it independently in their respective homes. This can be seen from the high enthusiasm of participants in participating in the socialization activity of making coconut shell briquettes. The results of the activities carried out show that the use of coconuts as charcoal briquettes offers an environmentally friendly alternative, with coconut shells as the main ingredient. This activity can also provide residents with new knowledge about the benefits and potential for reusing agricultural waste in their environment.ABSTRAKIndonesia sebagai negara agraris mempunyai potensi pemanfaatan kelapa terbesar di dunia. Tempurung kelapa adalah limbah pertanian yang merupakan salah satu sumber energi biomassa diolah menjadi briket. Tujuan dari pembuatan briket arang dari tempurung kelapa adalah untuk menciptakan sumber energi alternatif ramah lingkungan. Metode pelaksanaan kegiatan berupa sosialisasi masyarakat dusun sebanyak 10 orang peserta di Dusun Balla Tinggia pada Tahun 2025, yang bertujuan untuk menguraikan rencana yang dilakukan dengan cara menyajikan materi mencakup tahap-tahap pengolahan limbah tempurung kelapa menjadi bahan bakar briket ramah lingkungan. Program kerja pada kegiatan ini, yaitu: observasi, perencanaan, pelaksanaan dan pendampingan kegiatan, serta evaluasi hasil kegiatan. Berdasarkan wawancara dengan masyarakat Dusun Balla Tinggia, mereka memberikan apresiasi atas kesuksesan kegiatan ini, dengan penuh semangat mengikuti beberapa tahapan kegiatan yang dilakukan, sehingga mereka merasa mampu melakukannya secara mandiri di rumah masing-masing. Hasil dari kegiatan yang dilakukan menunjukkan bahwa pemanfaatan buah kelapa sebagai briket arang menawarkan alternatif yang ramah lingkungan, dengan tempurung kelapa sebagai bahan utama. Kegiatan ini juga, dapat membekali warga dengan pengetahuan baru mengenai manfaat dan potensi pemanfaatan kembali limbah pertanian yang ada di lingkungan sekitar mereka.